A New Stability Indicating Analytical Method Development And Validation for The Quantitative Determination of Emitricitabine And Lamivudine By RP-HPLC (World Journal of Current Medical and Pharmaceutical Research, 2020)
A novel stability indicating, precise, accurate and ecofriendly reverse phase high performance liquid chromatographic method was developed and validated for the quantitative determination of Emtricitabine and Lamivudine in pure and pharmaceutical dosage forms. Estimation of drugs in this combination was done with a C18 column [Kromasil C18column. 5mm, 4.6´250 mm]using mobile phase of compositionMethanol and phosphate buffer (40:60 v/v, pH 4).The flow rate was 1.0 ml/min and the effluents were monitored at 261 nm. The retention time of LamivudineandEmtricitabine were2.810 min and 4.727 min respectively. The linearity was found to be 40-80mg/ml for Lamivudine and40-80mg/ml forEmtricitabine.The stability parameters were evaluated by injecting the stressed sample and it was proved that there was no degradants. The established method was validated according to ICH guidelines.